The Role of Bawaslu Palangka Raya City in Overseeing the Abuse of Voting Rights in the 2024 Election - Ananta, Helga Citta; Kristian; Januardy, Ivans (Dinasti Research, 2025)
General elections are a manifestation of popular sovereignty as stipulated in the 1945 Constitution of the Republic of Indonesia, which is carried out directly, publicly, freely, confidentially, honestly and fairly. An election process that takes place with integrity is essential to ensure the legitimacy of the outcome and to maintain public confidence in the democratic system. However, abuse of voting rights, such as voting more than once at one or more polling stations, is one form of serious violation that can undermine the integrity of elections. This study aims to explore the role of the Election Supervisory Agency (Bawaslu) of Palangka Raya City in maintaining the validity of ballots in the Presidential, Vice Presidential, and Legislative Elections, as well as examining the supervisory strategies implemented to deal with violations committed by certain individuals. By using a systematic monitoring approach, strict law enforcement, and socialization related to violations in elections, Bawaslu is expected to ensure the implementation of elections that are fair, democratic, and in accordance with applicable legal principles. This research provides an in-depth description of the efforts made by Bawaslu in strengthening the election supervision process to prevent fraudulent practices and ensure the sustainability of a healthy democracy.